2015
DOI: 10.1098/rsta.2014.0339
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hydrodynamic stretch on the flame propagation enhancement of ethylene by addition of ozone

Abstract: One contribution of 14 to a theme issue 'Physics and chemistry of plasma-assisted combustion' .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…However, at pressures below 0.6 atm, Gao et al found that the flame speed was enhanced by O 3 . Other studies , also reached similar conclusions under reduced pressures.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, at pressures below 0.6 atm, Gao et al found that the flame speed was enhanced by O 3 . Other studies , also reached similar conclusions under reduced pressures.…”
Section: Introductionsupporting
confidence: 76%
“…Nonetheless, the understanding of how ozonolysis affects flame propagation is still incomplete. Reducing the pressure ,, simply redirects the O 3 consumption from ozonolysis reactions to the O 3 + H = O 2 + OH pathway. Several questions remain, including how decreased residence times alter ozonolysis-assisted flame propagation at atmospheric pressure and whether one-dimensional simulations are capable of accurately predicting experimental measurements when ozonolysis reactions are responsible for the majority of O 3 consumption.…”
Section: Introductionmentioning
confidence: 99%
“…On the application side, the enhancement of combustion by ozone is of interest, for example, in studies of the increase in burning velocities of methane/air flames and similar systems. …”
Section: Introductionmentioning
confidence: 99%